2020
DOI: 10.1016/j.humov.2020.102620
|View full text |Cite
|
Sign up to set email alerts
|

Motor imagery during action observation enhances imitation of everyday rhythmical actions in children with and without developmental coordination disorder

Abstract: Highlights• Imitation was less accurate in children with DCD compared to children without DCD • Motor imagery during action observation enhanced imitation in both groups• AO+MI is a promising tool for training children with different motor abilities

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 57 publications
3
26
0
Order By: Relevance
“…For the action observation (AO), imitation and gesture production category, there were nine papers (seven high quality, one moderate, and one low) (Reynolds et al, 2017a ; Blais et al, 2018 ; Costini et al, 2018 ; Gauthier et al, 2018 ; Nobusako et al, 2018 ; Lust et al, 2019 ; Scott et al, 2019 , 2020 ; Bieber et al, 2021 ). The effects of MI andAO(in isolation or combined) on motor imitation was investigated in six of these studies.…”
Section: Resultsmentioning
confidence: 99%
“…For the action observation (AO), imitation and gesture production category, there were nine papers (seven high quality, one moderate, and one low) (Reynolds et al, 2017a ; Blais et al, 2018 ; Costini et al, 2018 ; Gauthier et al, 2018 ; Nobusako et al, 2018 ; Lust et al, 2019 ; Scott et al, 2019 , 2020 ; Bieber et al, 2021 ). The effects of MI andAO(in isolation or combined) on motor imitation was investigated in six of these studies.…”
Section: Resultsmentioning
confidence: 99%
“…This would provide a greater ecological test of combined AO+MI instructions. Although research shows AO+MI training can have positive effects on motor skills in neurodevelopmental populations, such as children with developmental coordination disorder (Marshall, Wright, Holmes, Williams, et al., 2020 ; Scott et al., 2019 , 2020 ) and in stroke rehabilitation (Sun et al., 2016 ), the potential for changes in perceived interconnectedness in psychiatric conditions remains an unexplored question. In line with previous studies using the same paradigm, the main effect of compatibility was not significant in both the AO+MI condition (e.g., Eaves et al., 2014 ; Eaves, Riach, et al., 2016 ) and the intentional imitation condition (e.g., Eaves et al., 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are a large number of clinical trials that have investigated the use of either MI or AO alone in neurorehabilitation, but studies on the combination are still quite rare, especially in children or adolescents. Only recently; however, two studies reported on the positive effect of AOMI in children with DCD [ 100 , 101 ]. Scott et al (2020) reported that effect also for typically developing children without DCD and found a significant enhancement in the outcome measure compared to the usage of MI alone [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only recently; however, two studies reported on the positive effect of AOMI in children with DCD [100,101]. Scott et al (2020) reported that effect also for typically developing children without DCD and found a significant enhancement in the outcome measure compared to the usage of MI alone [101]. Surprisingly, the PETTLEP approach was used in only three of the studies for an enhancement of the MI intervention [76,86,88].…”
Section: Motor Imagery Training Interventionsmentioning
confidence: 99%